2011
DOI: 10.1016/j.neuroscience.2011.08.016
|View full text |Cite
|
Sign up to set email alerts
|

DJ-1 knock-down impairs astrocyte mitochondrial function

Abstract: Mitochondrial dysfunction has long been implicated in the pathogenesis of Parkinson’s disease (PD). PD brain tissues show evidence for mitochondrial respiratory chain Complex I deficiency. Pharmacological inhibitors of Complex I, such as rotenone, cause experimental parkinsonism. The cytoprotective protein DJ-1, whose deletion is sufficient to cause genetic PD, is also known to have mitochondria-stabilizing properties. We have previously shown that DJ-1 is over-expressed in PD astrocytes, and that DJ-1 deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 76 publications
(123 reference statements)
4
52
1
Order By: Relevance
“…In HeLa cells, DJ-1 RNAi specifically decreased expression of DJ-1 protein (Figure 2-figure supplement 1) and decreased mitochondrial membrane potential as probed with a J-aggregate forming lipophilic dye JC-1 ( Figure 2B) (Smiley et al, 1991), consistent with the previous reports (Larsen et al, 2011; peer-reviewed) is the author/funder. All rights reserved.…”
Section: Resultssupporting
confidence: 88%
“…In HeLa cells, DJ-1 RNAi specifically decreased expression of DJ-1 protein (Figure 2-figure supplement 1) and decreased mitochondrial membrane potential as probed with a J-aggregate forming lipophilic dye JC-1 ( Figure 2B) (Smiley et al, 1991), consistent with the previous reports (Larsen et al, 2011; peer-reviewed) is the author/funder. All rights reserved.…”
Section: Resultssupporting
confidence: 88%
“…Surprisingly, a number of these genes are linked to mitochondrial activity, the centres for energy production through aerobic glucose catabolism (48); these genes include PTEN-induced putative kinase (PINK1/ PARK6), an E3 ubiquitin ligase Parkin/PARK2 (49-51), LRRK2/PARK8 kinase controlling mitochondrial dynamics (52) and DJ-1/PARK7. Deficiency in DJ-1/PARK7, which causes early-onset Parkinson's disease, was reported to lead to abnormal mitochondrial morphology and dynamics, increased sensitivity to oxidative stress and impaired mitochondrial function (53)(54)(55)(56)(57). Functions of DJ-1 are further described below, as this protein can be viewed as a unique coordinator of glucose metabolism, mitochondrial function and Parkinson's disease.…”
Section: Role Of Parkinson's Diseaseassociated Dj-1 In Metabolismmentioning
confidence: 99%
“…2b). Several recent studies have reported that DJ-1 overexpression in astrocytes augments the capacity to protect neurons against rotenone and that DJ-1 knockdown impairs astrocyte-mediated neuroprotection against rotenone, 30,31 suggesting that DJ-1 may be involved in the neuroprotective effect of astrocytes on neurons. We quantified the number of THpositive neurons by immunofluorescence in the SN of control rats and rats overexpressing GFP-DJ-1.…”
Section: Dj-1 Attenuated Rotenone-induced Cell Injury In Mn9d Cellsmentioning
confidence: 99%